Injectable β-TCP/MCPM cement associated with mesoporous silica for bone regeneration: characterization and toxicity evaluation. (8th February 2018) - Mendes, L S; Saska, S; Coelho, F; Capote, T S de O; Scarel-Caminaga, R M; Marchetto, R; Carrodeguas, R G; Gaspar, A M M; Rodríguez, M A
Abstract: Calcium phosphate cement has been widely investigated as a bone graft substitute due to its excellent self-setting ability, biocompatibility, osteoconductivity and moldability. In addition, mesoporous materials have been studied as potential materials for application in medical devices due to their large surface area, which is capable of loading numerous biological molecules, besides being bioactive. In this study, bone β -TCP-MCPM-based injectable cement with mesoporous silica particles was synthesized and characterized in terms of its mechanical properties, microstructure, porosity, injectability, in vitro bioactivity and degradability; together with toxicity effects in CHO-K1 cell culture. The results showed that the β -TCP-MCPM cement is bioactive after soaking in simulated body fluid solution, and mesoporous silica particles provided better physicochemical properties compared with silica-free cement. Toxicity assays showed low CHO-K1 cell viability after treatment with more concentrated extracts (200 mg ml −1 ). However, this behavior did not compromise the reproductive capacity and did not promote significant DNA damage in those cells. In conclusion, the β -TCP-MCPM cement associated with mesoporous silica might be considered as a potential bone substitute for the repair and regeneration of bone defects.